Performativitas Gender: Membangun Identitas Gender dan Persona Bishonen pada Female-to-Male (F2M) Crossplayer - Asep Achmad Muhlisian (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
This study examines how female-to-male (F2M) crossplayers construct the bishounen persona as a form of gender performativity in crossplay. A quasiethnographic  approach was used, involving three participants from Bandung, selected via purposive sampling. Data were gathered through field observations, social media analysis, and in-depth interviews. The findings reveal that the respondents built their bishounen persona by aligning closely with the characters they portrayed, emphasizing costume and makeup. The bishounen persona characterized by feminine and androgynous features in male characters was consistently expressed by all three participants. This included visual traits such as long hair, a graceful appearance, a clean face, and a gentle, mysterious, and sensitive personality. The on-stage personas created by the respondents align with the concept of "front stage" identity performance. These performances were manifest through cosplay tests, stage and off-stage performances (costreet), photo sessions, and community interactions, all reinforcing the bishounen image within the Bandung cosplay community. These activities function as key mechanisms for building and projecting their front-stage personas in public. This phenomenon shows that gender identity is fluid, shifting across contexts and time.